2020
DOI: 10.1039/d0tb00408a
|View full text |Cite
|
Sign up to set email alerts
|

Spatial targeting of Bcl-2 on endoplasmic reticulum and mitochondria in cancer cells by lipid nanoparticles

Abstract: The presence of the same proteins at different sub-cellular locations with completely different functions adds to the complexity of signalling pathways in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Importantly, in this study, we show that AgNPs, apart from altering mitochondrial health, can also significantly disrupt the tubular nature of ER morphology and reissuances stress markers like GRP78, IRE 1 alpha, and Calnexin [22] . Interestingly, an earlier study by Pandey et al showed that ER and mitochondria-targeted NPs could potentially inhibit the function of anti-apoptotic proteins like Bcl2 facilitating cell death, indicating the importance and putative synergy between these organelles, which can be utilized in the future for cancer therapy [40] . On a similar note, to understand the ER-Mito crosstalk, we increased ER stress with a well-known ER stress inducer- Tunicamycin, alongside AgNP treatment, and it resulted in an enhanced de-regulation of mitochondrial homeostasis marked by increased mitochondrial ROS and fragmentation, leading to cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in this study, we show that AgNPs, apart from altering mitochondrial health, can also significantly disrupt the tubular nature of ER morphology and reissuances stress markers like GRP78, IRE 1 alpha, and Calnexin [22] . Interestingly, an earlier study by Pandey et al showed that ER and mitochondria-targeted NPs could potentially inhibit the function of anti-apoptotic proteins like Bcl2 facilitating cell death, indicating the importance and putative synergy between these organelles, which can be utilized in the future for cancer therapy [40] . On a similar note, to understand the ER-Mito crosstalk, we increased ER stress with a well-known ER stress inducer- Tunicamycin, alongside AgNP treatment, and it resulted in an enhanced de-regulation of mitochondrial homeostasis marked by increased mitochondrial ROS and fragmentation, leading to cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 is located on the outer mitochondrial membrane and regulates Bax/Bak to control mitochondrial fate, protecting permeability of the outer mitochondrial membrane and preventing cytochrome C release and apoptosis (del Gaizo Moore and Letai, 2013). Bcl-2 family proteins not only have well-known apoptotic functions, but also have little-known non-apoptotic functions in processes such as mitochondrial fusion, autophagy, endoplasmic reticulum stress response, and cell cycle regulation (Gross and Katz, 2017;Pandey et al, 2020). Numerous studies have suggested that Bcl-2 family members regulate the cell cycle and may play a critical role in tumor progression (Bonnefoy-Berard et al, 2004;Quinn and Richardson, 2004;Xie et al, 2020).…”
Section: Investigation Of Potential Mechanisms Of Cell Cycle Regulation By Bcl-2mentioning
confidence: 99%
“…Kale et al (2018) reviewed Bcl-2 function and the uncertain relationship between Bcl-2 and the plasma membrane. With advances in live cell imaging techniques and the generation of fluorescent recombinant proteins, studies have confirmed that Bcl-2 family proteins not only exist in mitochondria, but also dynamically distribute to other intracellular compartments such as endoplasmic reticulum, Golgi apparatus, nucleus, and peroxisome (Popgeorgiev et al, 2018;Pandey et al, 2020). In our study, the results of GO enrichment analysis revealed that Bcl-2 plays a critical role in cell cycle regulation by affecting the relative gene expression of the plasma membrane (Table 2), and this hypothesis requires additional investigation.…”
Section: Investigation Of Potential Mechanisms Of Cell Cycle Regulation By Bcl-2mentioning
confidence: 99%
“…Naphthalene sulfonamides, with similar structural characteristics, are also reported to interact with the sulfonylurea receptors on ER for targeted accumulation (Ghosh et al, 2019a). When surface‐modified with naphthalene sulfonamides, supramolecular nanoparticles (Ghosh et al, 2019b) and lipid nanoparticles (Pandey et al, 2020) exhibit satisfactory ER targeting effects.…”
Section: Endoplasmic Reticulum: the Protein And Lipid Production Factorymentioning
confidence: 99%
“…Apart from benzene sulfonamide, naphthalene sulfonamide is also used to modify nanoparticles for ER‐targeted applications. Pandey et al (2020) investigated the role of anti‐apoptotic Bcl‐2 protein at different subcellular locations in HeLa cells with ER‐ and mitochondria‐specific oleic acid‐based probes and Obatoclax (a pan‐Bcl‐2 inhibitor)‐loaded nanoparticles (i.e., ER‐Obt‐NPs and Mito‐Obt‐NPs). To selectively target the nanoparticles to ER, biocompatible oleic acid was reacted sequentially with ethylenediamine and dansyl chloride to obtain an oleic acid‐ethylenediamine‐dansyl conjugate, which owned a sulphonamide linkage that facilitated its interaction with the ER‐localized sulphonamide receptors.…”
Section: Endoplasmic Reticulum: the Protein And Lipid Production Factorymentioning
confidence: 99%